THE IMPORTANCE OF MULTIMEDIA TOOLS IN CONDUCTING SPIRITUAL AND EDUCATIONAL EVENTS - Pardayev Sobit Abdivali o‘g‘li, (PEDAGOGS, 2025)
Abstract: This article discusses the reforms being implemented in the process of spiritual and educational work, how to use modern technologies, and the types of modern technologies.